A new strategy to overcome the strength-ductility trade off of high entropy alloy. (June 2022) - Fu, Wujing; Li, Hongge; Huang, Yongjiang; Ning, Zhiliang; Sun, Jianfei
Abstract: Here, a new strategy, i.e., laser shock peening (LSP) followed by cyclic deep cryogenic treatment (DCT), is proposed to generate the gradient hierarchical structures and thus promote strength-ductility synergy of a high entropy alloy (HEA). We show that the non-equiatomic CrFeCoNiMn0.75 Cu0.25 HEA sample treated by this new strategy possesses an excellent combination of high strength (∼1100 MPa) and high plasticity (30%). Higher yield strength is achieved in HEA samples treated by LSP, due to the introduction of a gradient microstructure comprising sub-grains, dense dislocations and nano-twins (NTs) near the treated surface. Then, the following cyclic DCT processing can further introduce various types of reinforcing defect microstructures in core region of LSP-treated HEA, including dense intersecting NTs and stacking faults, thus effectively improving the tensile strength and plasticity. These results obtained here can shed new insights into develop high performance HEAs by tailoring residual stress and generating optimized microstructures. Graphical abstract: Image, graphical abstract